Cerebral perfusion and compensatory blood supply in patients with recent small subcortical infarcts. Issue 7 (July 2019) - Rudilosso, Salvatore; Laredo, Carlos; Mancosu, Marco; Moya-Planas, Nuria; Zhao, Yashu; Chirife, Oscar; Chamorro, Ángel; Urra, Xabier
Hypoperfusion is the typical perfusion pattern associated with recent small subcortical infarcts of the brain, but other perfusion patterns may be present in patients with these infarcts. Using CT perfusion, we studied 67 consecutive patients who had a small subcortical infarct at a follow-up MRI study to investigate the correlation between the perfusion pattern and the clinical and radiological course. On CT perfusion map analysis, 51 patients (76%) had focal hypoperfusion, 4 patients (6%) had hyperperfusion and the remaining 12 patients (18%) showed no abnormalities. On dynamic sequential imaging analysis obtained from the source perfusion images, 32 patients (48%) had a sustained hypoperfusion pattern, 11 patients (16%) had a reperfusion pattern, and 18 patients (27%) had a delayed compensation pattern. Systolic blood pressure was higher in patients with sustained hypoperfusion although the perfusion pattern was independent of the final volume of infarction. These results reinforce the notion that mechanisms other than hypoperfusion are at play in patients with small subcortical infarcts including the intervention of compensatory sources of blood flow. The ultimate clinical significance of these perfusion patterns remains to be determined in larger series of patients assessed longitudinally.